"The Orders of the Dreamed" George Nelson on Cree and northern Ojibwa religion and myth, 1823 - Nelson, George, 1786-1859.; Brown, Jennifer S. H., 1940-; Brightman, Robert Alain, 1950- (Winnipeg : University of Manitoba Press, 1988)
Transcription of 1823 diary by a Hudson's Bay Company fur trader in northeastern Saskatchewan which discusses the religion and mythic themes of the northern Ojibway and Cree. Also includes two essays: On Nelson's text by Stan Cuthand and On the ethics of publishing historical documents by Emma La Rocque.
On the ethics of publishing historical documents / by Emma LaRocque.
Includes bibliographical references (p. [205]-218) and index.
Description based on print version record.
Keywords: Cree Indians -- Religion; Cree Indians -- Mythology; Ojibwa Indians -- Religion; Ojibwa Indians -- Mythology; Indians of North America -- Canada -- Religion; Indians of North America -- Mythology -- Canada; Nelson, George, -- 1786-1859.; Cris (Indiens) -- Religion et mythologie; Ojibwa (Indiens) -- Religion et mythologie; Indiens -- Amérique du Nord -- Canada -- Religion et mythologie; Nelson, George, -- 1786-1859.; Nelson, George -- Schriftsteller; Religion; Ojibwa; Cree; RELIGION / Ethnic & Tribal; Electronic books